Kung fu panda 4 [videorecording (DVD)] - Aibel, Jonathan, 1969-; Berger, Glenn; Lemke, Darren; Zimmer, Hans; Mazzaro, Steve (Universal, 2024)
Po is gearing up to become the spiritual leader of his Valley of Peace, but also needs someone to take his place as Dragon Warrior. As such, he will train a new kung fu practitioner for the spot and will encounter a villain called the Chameleon who conjures villains from the past.